Contemporary critical discourse studies - Hart, Christopher; Cap, Piotr, 1970- (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc., 2014)
"CDS is a multifarious field constantly developing different methodological frameworks for analysing dynamically evolving aspects of language in a broad range of socio-political and institutional contexts. This volume is a cutting edge, interdisciplinary account of these theoretical and empirical developments. It presents an up-to-date survey of Critical Discourse Studies (CDS), covering both the theoretical landscape and the analytical territories that it extends over. It is intended for critical scholars and students who wish to keep abreast of the current state of the art. The book is divided into two parts. In the first part, the chapters are organised around different methodological perspectives for CDS (history, cognition, multimodality and corpora, among others). In the second part, the chapters are organised around particular discourse types and topics investigated in CDS, both traditionally (e.g. issues of racism and gender inequality) and only more recently (e.g. issues of health, public policy, and the environment).This is, altogether, an essential new reference work for all CDS practitioners"-- Resumé vydavatele
Keywords: diskurzivní analýza; kognitivní gramatika; discourse analysis; cognitive grammar; kolektivní monografie; collective monographs